Peran Investasi, Belanja Modal Dan Pendapatan Asli Daerah (PAD) Terhadap Pertumbuhan Ekonomi Di Provinsi Jambi - Andika Zia Ulhak; Siti Hodijah; Candra Mustika; Nurhayani . (JOURNAL OF SHARIA ECONOMICS, 2025)
This study aims to analyze the influence of investment, capital expenditure, and locally generated revenue (PAD) on economic growth in Jambi Province during the period of 2019–2024. Economic growth is measured through the Gross Regional Domestic Product (GRDP) at constant prices (ADHK) of 2010. The independent variables in this study include investment (domestic and foreign investment), government capital expenditure, and locally generated revenue. This research employs a quantitative approach using panel data analysis combining time series and cross-sectional data from all districts and cities in Jambi Province. The data were obtained from official institutions such as the Central Bureau of Statistics (BPS), the Directorate General of Fiscal Balance (DJPK), and the Investment Coordinating Board (BKPM). Data analysis was conducted using panel data regression methods, involving three model tests: the Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM), along with the Chow, Hausman, and Lagrange Multiplier tests to determine the most appropriate model. The results indicate that investment, capital expenditure, and PAD each have a positive effect on economic growth in Jambi Province, both partially and simultaneously. Increased investment contributes to production capacity expansion and job creation; government capital expenditure supports the provision of public infrastructure and economic efficiency; while PAD enhances the fiscal capacity of local governments to finance sustainable development. Simultaneously, these three variables significantly influence GRDP growth, highlighting the synergy between fiscal policy and investment activities in strengthening Jambi’s economic structure. The findings emphasize the importance of optimizing public and private investment, improving the effectiveness of capital expenditure, and enhancing local fiscal independence to support inclusive and sustainable economic growth.